Juvenile Justice (Care and Protection of Children) Act 2015 –An Awareness Call to Prospective Teachers - Dhavamani, Sigamani; Rositta, M. Ugin (Science Insights Education Frontiers, 2025)
Education has become the right of every child so as to live with dignity and harmony. Family and Classroom are the two major zones determine mental health status of the children. Facilitating a holistic and healthy environment prevents them from delinquency. Besides academics, teachers must be equipped with 360-degree potentialities to face classroom challenges regarding health, social, and legal aspects while handling disruptive students. Understanding juvenile justice law ensures better student handling and guarantees care and protection. This study is a call for prospective teachers to understand the basic crux of the JJ Act, 2015, with relevance to Care and Protection of Children in Tamil Nadu. By executing the convergent mixed method design, desk research (Qualitative phase) was employed to examine the coverage of JJ Act 2015 in the coursework of the prospective Teachers. Simultaneously, simple random sampling technique was adopted to collect data from 340 prospective teachers (Quantitative phase). The level of awareness was assessed through a standardized checklist. Besides, hypotheses were framed to test the significant role of certain demographic variables. The contradictory findings extend its recommendations to the academic boards to include JJ act, 2015 in the coursework of the prospective teachers. Furthermore, suggestions were framed with an intention to create more awareness and necessary actions to prevent classroom delinquency.